PENYELESAIAN SENGKETA LINGKUNGAN HIDUP DI LUAR PENGADILAN BERDASARKAN UNDANG UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP (STUDI KASUS: PUTUSAN NOMOR 178/Pdt.G/LH/2019/PN Blb) - Melvina Melvina (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
The Indonesian state is rich in natural resources which are managed for the welfare of the people. However, there are times when the use of natural resources is carried out inefficiently and is only oriented towards short-term interests carried out by irresponsible human behavior which results in uncontrolled damage and pollution to natural resources. Environmental damage and pollution can lead to potential environmental disputes.The purpose of this paper is to find out how to resolve environmental disputes outside the court based on undang-undang nomor 32 tahun 2009 tentang perlindungan dan pengelolaan lingkungan hidup (studi kasus: putusan nomor 178/Pdt.G/LH/2019/PN Blb).The method used is a normative legal research method with qualitative normative analysis techniques and is subject to statutory research. The conclusion of this paper is undang-undang nomor 32 tahun 2009 tentang perlindungan dan pengolaan lingkungan hidup.a way to settle environmental disputes outside the court is provided in order to reach an agreement on the form and amount of compensation and/or on certain actions to ensure that negative impacts on the environment will not be repeated.